Wireless communication based on chirp signals for LoRa IoT Devices - Fialho, Vitor (2019)
This paper presents the study of chirp signals for wireless communications between Internet of Thing devices used on low power wide area networks. Up and down chirp concept is introduced as well as the chirp spread spectrum concept. A computationally efficient symbol decoding method is presented based of discrete Fourier transform as an alternative to typical coherent detection. The proposed LoRa simulation model is implemented in MATLAB allowing the communication system evaluation based on bit error rate and packet error rate.